High flow nasal cannula therapy in the pediatric home setting. Issue 3 (29th December 2022) - Ehrlich, Shay; Golan Tripto, Inbal; Lavie, Moran; Cahal, Michal; Shonfeld, Tommy; Prais, Dario; Levine, Hagit; Mei‐Zahav, Meir; Bar‐On, Ophir; Gendler, Yulia; Zalcman, Jonatan; Sarsur, Eahab; et al.
Abstract: Background: High‐flow nasal cannula (HFNC) therapy may be better tolerated than traditional noninvasive ventilation (NIV) and is rapidly gaining acceptance in pediatric acute care. In Israel, HFNC is approved for domestic use. We aim to describe its indications, efficacy, parental satisfaction, and safety. Methods: Retrospective study of children treated with home HFNC therapy in three pediatric centers. Data included demographic parameters, indication of use, weight and days of hospitalization before and after initiation. Safety, tolerability, and parental satisfaction were assessed via standardized telephone questionnaire. Results: Median (interquartile range [IQR]) age of initiating home HFNC in 75 children was 8.3 (2.2, 29.6) months. Indications were obstructive sleep apnea (33; 44%), airway malacia (19; 25%), chronic lung disease (15; 20%), neuromuscular disease (4; 5%), and postextubation support (4; 5%). Weight standard deviation score rose from −2.3 pre‐HFNC to −1.7 at 6.7 months post‐HFNC initiation, p  < 0.001. Hospital admission days during the 2 months pre‐ versus post‐HFNC initiation were 22 (5.5, 60) and 5 (0, 14.7) respectively, p  < 0.008. Median (IQR) parental satisfaction score was 5/5 (4, 5). Fifty of 60 (83%) respondents would recommend home HFNC to other families in a similar situation. There were no serious adverse events. Conclusion: In our population, domestic HFNC appeared safe and well tolerated for a variety of indications. Its introduction was associated with improved weight gain, fewer hospitalization days and high parental satisfaction. Further work is required to characterize groups of children most likely to benefit from HFNC, as opposed to traditional modes of NIV.